2012
DOI: 10.1603/me11080
|View full text |Cite
|
Sign up to set email alerts
|

Culex Flavivirus and West Nile Virus inCulex quinquefasciatusPopulations in the Southeastern United States

Abstract: Little is known of the interactions between insect-only flaviviruses and other arboviruses in their mosquito hosts, or the potential public health significance of these associations. The specific aims of this study were to describe the geographic distribution, prevalence, and seasonal infection rates of Culex flavivirus (CxFV) and West Nile virus (WNV) in Culex quinquefasciatus Say in the Southeastern United States, investigate the potential association between CxFV and WNV prevalence in Cx. quinquefasciatus a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
39
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 35 publications
1
39
0
1
Order By: Relevance
“…A field study conducted in Chicago found a positive ecological association between the infection rates with WNV and CxFV, in Culex pipiens mosquito pools. 41 In contrast, Crockett and others 42 found no evidence to support an association between WNV and CxFV prevalence rates in Culex quinquefasciatus populations in the southeastern United States. In vitro and in vivo studies looking at the potential interaction of WNV with insect-specific flaviviruses in mosquito cells and in mosquitoes have also produced conflicting results.…”
Section: Discussionmentioning
confidence: 94%
“…A field study conducted in Chicago found a positive ecological association between the infection rates with WNV and CxFV, in Culex pipiens mosquito pools. 41 In contrast, Crockett and others 42 found no evidence to support an association between WNV and CxFV prevalence rates in Culex quinquefasciatus populations in the southeastern United States. In vitro and in vivo studies looking at the potential interaction of WNV with insect-specific flaviviruses in mosquito cells and in mosquitoes have also produced conflicting results.…”
Section: Discussionmentioning
confidence: 94%
“…collected in the field (Newman et al, 2011). However, a study conducted in the southern United States found no such correlation (Crockett et al, 2012). Several arboviruses, including WNV (Bolling et al, 2012;Hobson-Peters et al, 2013;Kenney et al, 2014;Kent et al, 2010), Murray Valley encephalitis virus (Hobson-Peters et al, 2013), Japanese encephalitis virus (Kenney et al, 2014), and St. Louis encephalitis virus (Kenney et al, 2014), have been shown to exhibit inhibited replication in the C6/36 mosquito cell line when preinfected or coinfected with ISVs.…”
Section: Impact Of Isvs On Experimental Studies-in Vitro and Lab Colomentioning
confidence: 99%
“…However, evidence of super-infection exclusion has not always been reported in cases of viral co-infections. For example, Kent et al (2010) found that CxFV Izabal strain did not affect the vector competence of Culex quinquefasciatus for transmitting WNV when mosquitoes were infected sequentially in the laboratory, and Crockett et al (2012) found no evidence supporting an association between WNV and CxFV infection prevalence in wild mosquitoes.…”
Section: Introductionmentioning
confidence: 99%